[Aerial view of Cal Poly campus] (1973)
View of Cal Poly campus and surrounding residences, Yosemite, Sierra Madre, Engineering East, Spanos Theater, Engineering West, red-brick dorms, North Mountain, Agricultural Engineering, Poly "P" - looking north